2021
DOI: 10.31031/apdv.2021.08.000680
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Small Ruminants Production: A Review

Abstract: Sheep and goats, known as small ruminants, are an important component group of livestock, representing 58% of the global domestic ruminant population. Both sheep and goats are adapted well under varied climatic conditions including harsh climates. The large-scale presence of these animals in the arid regions indicates the adaptability of these animals to the hotter climatic conditions. the impact of climate change and consequential heat stress conditions, however, has been found to affect the growth and produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…Thus, heat stress can disrupt ruminant body homeostasis by evoking several thermophysiological mechanisms that try to maintain BTH. These mechanisms are well documented, where numerous research articles on ruminants have reported that heat stress can lead to a reduction in feed intake, body weight, and energy metabolism, an increase in body water turnover and urination, a redistribution of blood supply far away from internal organs, as well as an acceleration of evaporative cooling via respiration and sweating [6,11,12]. Thereby, noticeable changes can be observed in ruminants' biophysiological functions under heat stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, heat stress can disrupt ruminant body homeostasis by evoking several thermophysiological mechanisms that try to maintain BTH. These mechanisms are well documented, where numerous research articles on ruminants have reported that heat stress can lead to a reduction in feed intake, body weight, and energy metabolism, an increase in body water turnover and urination, a redistribution of blood supply far away from internal organs, as well as an acceleration of evaporative cooling via respiration and sweating [6,11,12]. Thereby, noticeable changes can be observed in ruminants' biophysiological functions under heat stress conditions.…”
Section: Introductionmentioning
confidence: 99%